2013
DOI: 10.1002/cncr.28010
|View full text |Cite|
|
Sign up to set email alerts
|

Health‐related quality of life of patients with advanced breast cancer treated with everolimus plus exemestane versus placebo plus exemestane in the phase 3, randomized, controlled, BOLERO‐2 trial

Abstract: BACKGROUND:The randomized, controlled BOLERO-2 (Breast Cancer Trials of Oral Everolimus) trial demonstrated significantly improved progression-free survival with the use of everolimus plus exemestane (EVE þ EXE) versus placebo plus exemestane (PBO þ EXE) in patients with advanced breast cancer who developed disease progression after treatment with nonsteroidal aromatase inhibitors. This analysis investigated the treatment effects on health-related quality of life (HRQOL). METHODS: Using the European Organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 34 publications
1
67
0
1
Order By: Relevance
“…Based on data from the BOLERO-2 trial, the mTOR inhibitor everolimus (EVE) in combination with exemestane (EXE) was approved by the US Food and Drug Administration and European Medicines Agency to treat postmenopausal women with HR?ve/ HER2-ve advanced breast cancer that recurred or progressed during or after a non-steroidal AI therapy [3]. The combination of EXE/EVE has doubled the median PFS compared to EXE/placebo at 18 months median follow-up, with good health-related quality of life (HRQoL), and a consistent efficacy in all predefined patient subgroups (i.e., visceral metastases, patients with bone disease, and elderly patients) [4][5][6]. Moreover, the improvement on PFS by the EXE/EVE has been also confirmed into the final analysis performed by Yardley et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from the BOLERO-2 trial, the mTOR inhibitor everolimus (EVE) in combination with exemestane (EXE) was approved by the US Food and Drug Administration and European Medicines Agency to treat postmenopausal women with HR?ve/ HER2-ve advanced breast cancer that recurred or progressed during or after a non-steroidal AI therapy [3]. The combination of EXE/EVE has doubled the median PFS compared to EXE/placebo at 18 months median follow-up, with good health-related quality of life (HRQoL), and a consistent efficacy in all predefined patient subgroups (i.e., visceral metastases, patients with bone disease, and elderly patients) [4][5][6]. Moreover, the improvement on PFS by the EXE/EVE has been also confirmed into the final analysis performed by Yardley et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…The median TDD for a 5% change from baseline was 8.3 months (95% CI, 7.0-9.7) in the everolimus + exemestane arm compared with 5.8 months (95% CI, 4.2-7.2) in the placebo + exemestane arm. Despite a higher incidence of AEs in the combina- tion arm, QoL analysis concluded that the treatment arm was associated with a longer TDD in global health-related QoL when compared with exemestane alone [77] .…”
Section: Qol With Endocrine-based Targeted Combination Therapy Everolmentioning
confidence: 98%
“…[77,78] . The validity, reliability, and relevance of these scales for patients with cancer have been clearly demonstrated [78,79] .…”
Section: Patient Qol In Et Studiesmentioning
confidence: 99%
See 2 more Smart Citations